Mediasi Melalui Pendekatan Mufakat Sebagai Lembaga Alternatif Penyelesaian Sengketa Untuk Mendukung Pembangunan Ekonomi Nasional - Arliman S, larensius (UIR Press, 2018)
Economic development is the main pillar in supporting the growth and development of a nation. The dynamics of economic development sometimes cause disputes due to business conflicts and feuds. Conventional dispute resolution is done in one place, court. Non-court settlement disputes generally use different ways of dispute resolution through courts, ie, the use of several means among others is mediation in economic disputes. This paper discusses how the role of mediation as an alternative institution of dispute resolution to support national economic development and the role of the approach mufakat. This research uses nominal juridical method with analytical descriptive approach. The results of this study indicate that the role of mediation as an alternative institution of dispute resolution is important and some are not, especially in commercial court disputes; dispute that industrial relations courts; business competition; consumer disputes, and other disputes whose hearings in the hearing are determined by the deadline for settlement in the provisions of laws and regulations, such as disputes in banking and insurance. The approach of mufakat is very important in carrying out mediation of economic dispute resolution, because consensus is a symbol of the Indonesian nation.